Consistency may be key, but continuity is essential for success. Issue 9 (11th November 2021) - Skipworth, Stan
Abstract : Throughout the course of my career, I've long heard of, and applied myself to, the concept of being consistent, to being able to perform my job at a particular level or standard to the best of my ability, even if the circumstances of doing so become more demanding or complex.